Sosialisasi Pembelajaran Sastra Berperspektif Jender Bagi Guru SMA/SMK se-Surakarta - Purwahida, Rahmah; Huda, Miftakhul (WARTA, 2010)
Socialization purposes, namely (1) socialization that participants are able tounderstand and master the learning literature a gender perspective in terms ofcurriculum, teaching materials, and learning strategies in the classroom and (2)conducted a follow-up of this activity in the form of training activities, learningmaterials utilization literature a gender perspective. Socialization is given to highschool teachers and vocational as Surakarta. The method adopted in this traininginclude: seminars, frequently asked questions, and discussion. Socialization lastedone day with the number of participants 19 persons. Evaluation of this activity isdone in the process. During the training activities the participants enthusiastic,passionate, active and responsive. Through this socialization of teachers get thenecessary materials related strategies, methods and teaching materials literature agender perspective. The teachers are motivated to understand gender issues in acomprehensive manner. Insights teachers to manage learning an enjoyable literarygender perspective in the classroom increases. It is because any discussion of solutions of the constraints experienced by teachers in teaching literature a gender perspective.